The Southasian sensibility a Himal reader - Dixit, Kanak Mani (New Delhi Sage Publications India Pvt. Ltd., 2012)
A collection of some of the best articles published over the past 25 years in Himal Southasian, South Asia's first and foremost regional news and analysis magazine.
Keywords: South Asia -- History -- 20th century; South Asia -- History -- 21st century; South Asia -- Politics and government -- 20th century; South Asia -- Politics and government -- 21st century